Subsidies, information, and energy-efficient cookstove adoption: A randomized uncontrolled trial in rural Ethiopia - Mandy Malan; Marten Voors; Jörg Ankel-Peters; Selan J. Seje; Lotte Heuburger; Dawud Seid; Abiyot Mitiku (RWI - Leibniz-Institut für Wirtschaftsforschung, 2023)
Energy-efficient biomass cookstoves (EEBC) are an important technology for the three billion people relying on firewood and charcoal for cooking in the Global South. This paper assesses the price-responsiveness of demand for EEBC and the role of information about health and economic benefits. The pilot program under evaluation randomized different subsidy schemes (40%, 70%, and 100% subsidy) and information treatments across 292 Ethiopian villages. Unlike previous willingness-to-pay studies we examine a take-it-orleave-it approach in an uncontrolled and hence natural setting. We observe that EEBC demand is highly price-sensitive: There is virtually no EEBC uptake in the no-subsidy group, irrespective of which information households received. Yet, uptake increases considerably for households who received a high subsidy (70% or a 100%). Adding information on economic benefits nearly doubles uptake when coupled with such high subsidies. Our results confirm the emerging picture in the literature suggesting that subsidization for EEBC is required to foster widespread adoption. – – Energieeffiziente Biomasse-Kochherde (EEBC) sind eine wichtige Technologie für die drei Milliarden Menschen, die im globalen Süden auf Feuerholz und Holzkohle zum Kochen angewiesen sind. In diesem Papier wird die Preisreaktion der Nachfrage nach EEBC und die Rolle von Informationen über gesundheitliche und wirtschaftliche Vorteile untersucht. Im Rahmen des evaluierten Pilotprogramms wurden in 292 äthiopischen Dörfern nach dem Zufallsprinzip verschiedene Subventionsregelungen (40 %, 70 % und 100 % Subvention) und Informationsmaßnahmen durchgeführt. Im Gegensatz zu früheren Zahlungsbereitschaftsstudien untersuchen wir einen "take-it-orleave-it"-Ansatz in einem unkontrollierten und daher natürlichen Umfeld. Wir stellen fest, dass die Nachfrage nach EEBC sehr preisempfindlich ist: In der Gruppe ohne Subventionierung werden EEBC praktisch nicht in Anspruch genommen, unabhängig davon, welche Informationen die Haushalte erhalten haben. Bei Haushalten, die einen hohen Zuschuss (70 % oder 100 %) erhalten, steigt die Inanspruchnahme jedoch erheblich. Durch die Hinzufügung von Informationen über wirtschaftliche Vorteile verdoppelt sich die Akzeptanz nahezu, wenn sie mit solch hohen Subventionen gekoppelt ist. Unsere Ergebnisse bestätigen das sich in der Literatur abzeichnende Bild, dass eine Subventionierung von EEBC erforderlich ist, um eine breite Akzeptanz zu fördern.
Keywords: C93; O12; O13; Q41; Q48; 330; Household technology adoption; biomass consumption; randomized controlled trial; humanitarian assistance; environmental degradation